Smallpox DNA Vaccine Protects Nonhuman Primates against Lethal Monkeypox - Hooper, J. W. (American Society for Microbiology, 2004)
Two decades after a worldwide vaccination campaign was used to successfully eradicate naturally occurring smallpox, the threat of bioterrorism has led to renewed vaccination programs. In addition, sporadic outbreaks of human monkeypox in Africa and a recent outbreak of human monkeypox in the U.S. have made it clear that naturally occurring zoonotic orthopoxvirus diseases remain a public health concern. Much of the threat posed by orthopoxviruses could be eliminated by vaccination; however, because the smallpox vaccine is a live orthopoxvirus vaccine (vaccinia virus) administered to the skin, the vaccine itself can pose a serious health risk. Here, we demonstrate that rhesus macaques vaccinated with a DNA vaccine consisting of four vaccinia virus genes (L1R, A27L, A33R, and B5R) were protected from severe disease after an otherwise lethal challenge with monkeypox virus. Animals vaccinated with a single gene (L1R) which encodes a target of neutralizing antibodies developed severe disease but survived. This is the first demonstration that a subunit vaccine approach to smallpox-monkeypox immunization is feasible.